2018
DOI: 10.1155/2018/6215350
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Immune Cells in Postoperative Cognitive Dysfunction

Abstract: Postoperative cognitive dysfunction (POCD), a long-lasting cognitive decline after surgery, is currently a major clinical problem with no clear pathophysiological mechanism or effective therapy. Accumulating evidence suggests that neuroinflammation plays a critical role in POCD. After surgery, alarmins are leaked from the injury sites and proinflammatory cytokines are increased in the peripheral circulation. Neurons in the hippocampus, which is responsible for learning and memory, can be damaged by cytokines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 87 publications
2
41
0
Order By: Relevance
“…*** P < 0.001 versus control group. # P < 0.05, ## P < 0.01 and ### P < 0.001 versus normal saline (NS) group impairment and neuronal death (Castanon, Luheshi, & Layé, 2015;Fabrègue, Butkowski, Voigt, & de Jong, 2016;Liu & Yin, 2018). In the present study, treatment with RC reduced heat stress-induced protein expression of the pro-inflammatory cytokine TNF-in the hippocampus, which was associated with attenuation of HS-triggered cognitive deficits.…”
Section: Synaptic Integration Markerssupporting
confidence: 49%
See 1 more Smart Citation
“…*** P < 0.001 versus control group. # P < 0.05, ## P < 0.01 and ### P < 0.001 versus normal saline (NS) group impairment and neuronal death (Castanon, Luheshi, & Layé, 2015;Fabrègue, Butkowski, Voigt, & de Jong, 2016;Liu & Yin, 2018). In the present study, treatment with RC reduced heat stress-induced protein expression of the pro-inflammatory cytokine TNF-in the hippocampus, which was associated with attenuation of HS-triggered cognitive deficits.…”
Section: Synaptic Integration Markerssupporting
confidence: 49%
“…According to evidence, heat stress also affects systemic inflammatory responses, increasing levels of pro‐inflammatory cytokines, such as IL‐6 and TNF‐α, in the brain and blood (Chauhan et al., ; Lee et al., ; Moon et al., ; Starkie et al., ). Furthermore, excessive inflammation in the brain is linked to cognitive impairment and neuronal death (Castanon, Luheshi, & Layé, ; Fabrègue, Butkowski, Voigt, & de Jong, ; Liu & Yin, ). In the present study, treatment with RC reduced heat stress‐induced protein expression of the pro‐inflammatory cytokine TNF‐α in the hippocampus, which was associated with attenuation of HS‐triggered cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%
“…However, a wealth of literature has described the link between sevoflurane and postoperative complications, including POCD . A number of molecular mechanisms have been proposed to account for the cognitive decline induced by sevoflurane, among which the neuroinflammation induced by anesthesia combined with surgery is generally believed to serve as the trigger and is supported by several reports . For instance, Yang et al reported that anesthesia/surgery impaired the permeability of the blood–brain barrier, and caused an elevated production of interleukin‐6 in an age‐associated manner, accompanied by the prominent deficits in cognitive functions .…”
Section: Discussionmentioning
confidence: 99%
“…Some emphasized the effect of hypotension/hypoxia, hypercarbia, and anesthetic toxicity as contributing factors. However, neuroinflammation occupies the most dominant place in a discussion of postoperative cognitive decline 3,11,18 . Post-cardiac surgery inflammation leads to an elevation in free radicals, acute phase proteins, complement abnormalities, and cellular abnormalities 3,18,19 .…”
Section: Introductionmentioning
confidence: 99%